2022
DOI: 10.1001/jama.2022.2518
|View full text |Cite
|
Sign up to set email alerts
|

Association of Echocardiographic Measures of Left Atrial Function and Size With Incident Dementia

Abstract: Key PointsQuestionAre lower (worse) left atrial (LA) function and greater LA size associated with increased risk of subsequent dementia?FindingsIn this retrospective cohort study that included 4096 participants, there were statistically significant associations between measures of lower LA function and incident dementia comparing the lowest vs highest quintile for LA reservoir strain (HR, 1.98), conduit strain (HR, 1.50), contractile strain (HR, 1.57), emptying fraction (HR, 1.87), and active emptying fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…Atrial strain is an emerging topic within world-wide research setting. Atrial strain has been shown prognostic value in both patients with AF [23] and the general population, predicting cardiovascular mortality, morbidity, and for example development of dementia [24,25]. In this observational study we focused on the determinants of atrial strain and showed an association of atrial strain with individual and combined comorbidities, irrespective of atrial dilatation.…”
Section: Discussionmentioning
confidence: 88%
“…Atrial strain is an emerging topic within world-wide research setting. Atrial strain has been shown prognostic value in both patients with AF [23] and the general population, predicting cardiovascular mortality, morbidity, and for example development of dementia [24,25]. In this observational study we focused on the determinants of atrial strain and showed an association of atrial strain with individual and combined comorbidities, irrespective of atrial dilatation.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, echocardiography can identify atrial myopathy, which is characterized by alterations of left atrial function/size, has been recognized as a possible mechanism for ischemic stroke independently of the presence of atrial fibrillation. Impaired left atrial function may be a risk factor associated with dementia, as recently demonstrated by an exploratory analysis of a US community-based cohort [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, causal mediation analyses 21 were used to investigate the proportion of the exposure-outcome association mediated by of intermediate CVDs and diabetes, which occurred between baseline and the onset date of HF (“mediation” R package). 22 To recover correct CIs for the estimates, the mediation analyses were estimated via bootstrapping (2,000 replications). Supplemental Methods, Section 4 displays the detailed description of the mediation analysis.…”
Section: Methodsmentioning
confidence: 99%